E-Business Initiatives in Indonesian Manufacturing SMEs - Singgih Saptadi; Iman Sudirman; TMA Ari Samadhi; Rajesri Govindaraju (Institute of Research and Community Outreach - Petra Christian University, 2014)
The role of information technology (IT) in improving companies’ competitiveness, including small and medium enterprises (SMEs), has been widely accepted. But, the IT investment will be in vain, if SMEs do not align their business and IT. There is a need to develop a framework of business-IT alignment. The framework development requires an understanding of the patterns of IT implementation in supporting SMEs’ business (e-business initiatives). This paper presents an empirical study on e-business initiatives in Indonesian manufacturing SMEs. The study uses 41 business processes that are grouped into three business focuses: supplier side, internal side and customer side. Based on the complexity of IT support to business processes, supplier side score, internal side score, customer side score and global score can be calculated. These scores are used to develop e-business initiative groups by using cluster analysis. After validated using discriminant analysis, the cluster analysis gives five e-business initiatives. First initiative is e-business implementation in three sides of business focuses, although in the early stage. Second initiative is IT implementation with internal side focus. Third initiative is e-business with customer side focus. The fourth is initiative that focuses on internal and customer side. The last is e-business initiative that balances and extends IT implementation on the three sides of business focuses. Then, this paper explains the differences between e-business initiatives.